2003
DOI: 10.1159/000069725
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Patients with Acute Coronary Syndrome and Moderate Coronary Artery Stenosis

Abstract: We evaluated the clinical outcome and the prognostic factors at 6-year follow-up of patients with acute coronary syndrome without critical coronary arterial narrowing. The mean follow-up was 73 ± 19 months. Mortality rate was 13%, and 20 patients (12%) had major cardiac event, 8 patients (5%) had stroke and 10 patients (6%) underwent revascularization. Multivariate analysis matched for age and ejection factor showed that moderate disease (stenosis 40–59%) (OR = 2.713, p < 0.024) was an independent predictive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Also, the sample size was too small to evaluate differences in clinical characteristics and outcome between patients with completely normal coronary angiograms and those with minor CAD. The majority of patients with NOCAD in our study had minor CAD and these patients have been shown to have a higher risk of subsequent clinical events compared to patients with completely normal coronary arteries [6,7]. It is also true that coronary lesions may not always be reliably detected by coronary angiography [27].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the sample size was too small to evaluate differences in clinical characteristics and outcome between patients with completely normal coronary angiograms and those with minor CAD. The majority of patients with NOCAD in our study had minor CAD and these patients have been shown to have a higher risk of subsequent clinical events compared to patients with completely normal coronary arteries [6,7]. It is also true that coronary lesions may not always be reliably detected by coronary angiography [27].…”
Section: Limitationsmentioning
confidence: 99%
“…One study revealed a 2% in-hospital risk of death or myocardial infarction in patients with NOCAD presenting with unstable angina (UA) or non-Q-wave myocardial infarction (MI) [5], while in a larger study a 2% 12-month rate of death or MI and a 12% composite event rate was found in similar patients after non-ST elevation ACS [6]. A study with much longer follow-up of such patients noted a 13% mortality and 12% major coronary event rate at 6 years [7]. It is likely that aggressive risk factor reduction may improve outcome, but utilisation of preventative medical therapy in this subset of ACS patients has not been well characterised.…”
Section: Introductionmentioning
confidence: 99%